HUBUNGAN ASUPAN ENERGI, PROTEIN DAN PEMBERIAN ASI EKSKLUSIF DENGAN KEJADIAN STUNTING PADA BALITA DI BOJONEGORO - Vernanda, Dina Anjelia (Jurnal Gizi dan Kesehatan Nusantara, 2023)
Stunting is a condition of malnutrition in toddlers so that toddlers have less height compared to their age. In 2022, the stunting rate in the Balen Health Center work area is 119 stunting cases. This study aims to determine the relationship between the level of energy intake, protein and history of exclusive breastfeeding with the incidence of stunting in toddlers in the Balen District area of Bojonegoro Regency. The research method uses observational analytics with a case control approach. The respondents of this study were 51 stunted toddlers and 51 non-stunted toddlers by taking respondents using total sampling techniques and applying matching to the gender and age of toddlers. Toddler height data was collected by direct measurement, while exclusive feeding intake and breastfeeding history data were conducted by interviews using food recall forms and exclusive breastfeeding history questionnaires. Data analysis was performed with a chi-square test. The results showed that there was a significant relationship between the level of energy intake and the incidence of stunting in toddlers in the Balen District area of Bojonegoro Regency (p value = 0.000; OR = 16.640), there was no significant relationship between the level of protein intake and the incidence of stunting in toddlers in Balen District, Bojonegoro Regency (p value = 0.243; OR = 7.43), and there was no significant relationship between the history of exclusive breastfeeding and the incidence of stunting in toddlers in Balen District, Bojonegoro Regency (p value = 0.161; OR = 1.944).